Deutero-Learning in Organizations: A Review and a Reformulation - Visser, Max (Academy of Management Review, 2007)
Higher-order learning in and by organizations is often conceptualized in the literature as deutero-learning. However, current definitions and descriptions of this concept suffer from conceptual confusion and terminological ambiguity, impeding a proper theoretical understanding and hindering empirical research. Following Bateson and Argyris and Schön, I reformulate the concept of deutero-learning as the behavioral adaptation to patterns of conditioning in relationships in organizational contexts, distinguishing it from meta-learning and planned learning.